The Relationship between Students’ Willingness to Communicate (WTC) in English and Their Teacher Immediacy Behaviours - Ainun Nurdzizati; Nur Aeni; Ryan Rayhana Sofyan; Nur Aeni (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to investigate the relationship between students’ WTC and teacher immediacy behaviors, to reveal what kind of immediacy behaviors are used in English classrooms, and to understand how students perceive teacher immediacy that affects students’ WTC. The researcher employed a QUAL-quan model or exploratory mixed methods design. The data was collected through observation, questionnaire, and interview to achieve the research objective. The sample of this study was 30 students in second grade in MAN Pangkep. The questionnaire analysis using Pearson Product Moment found that students’ WTC and TI have a positive correlation of 0.7013. And observation results showed that the teacher used various immediacy, including verbal and non-verbal behaviors. And students have a positive viewpoint on teacher immediacy affects their willingness to communicate.